O Paraná no Brasil: uma contextualização em treze imagens (e meia) - Hervé Théry; André Nagy; Raimundo Nonato Junior (Confins)
The paper puts the state of Paraná in the Brazilian context, using thematic mapping to analyze the differences and dynamics that mark the territory in several areas. Research maps, provided they follow the precepts of graphical semiotics, also serve to communicate the results in a visually expressive way. These unpublished maps were chosen to present the State in various contexts, demographic, economic and social, where it now appears homogeneous and stands out clearly from the rest of the country, now has internal contrasts that make part of its territory resemble other Brazilian regions